To Discriminate General Election system in Thailand by using K-Means Clustering (Journal of Pharmaceutical Negative Results, 2022)
Thailand uses the ballot paper in the general election since 1933. In the present day, technology has been involved in daily basics. This study aims to explore the hypothesis of the election system in Thailand which can use the technology in the election process name as electronic voting (e-voting) or still need to use the traditional method. Before implementation, it should study in terms of the area that is ready to implement the new method and where still need to use the current one. This study takes the relevant factors to analyze with the data of each area collected from various sources. The clustering method used in this study is k-means. Then to find the acceptable k cluster the silhouette method is used. The result is 2 cluster is a perfect fit with the 11 factors that used in this study. The first cluster is Bangkok which is the capital city to be matched with the e-voting method and the second cluster is the remainder province in Thailand (76 provinces). This can be used for the next study in terms of supply chain design for e-voting and developing the ballot paper logistics.